A new method of recording from the giant fiber of Drosophila melanogaster shows that the strength of its auditory inputs remains constant with age. - Jonathan M Blagburn (PLoS ONE)
There have been relatively few studies of how central synapses age in adult Drosophila melanogaster. In this study we investigate the aging of the synaptic inputs to the Giant Fiber (GF) from auditory Johnston's Organ neurons (JONs). In previously published experiments an indirect assay of this synaptic connection was used; here we describe a new, more direct assay, which allows reliable detection of the GF action potential in the neck connective, and long term recording of its responses to sound. Genetic poisoning using diphtheria toxin expressed in the GF with R68A06-GAL4 was used to confirm that this signal indeed arose from the GF and not from other descending neurons. As before, the sound-evoked action potentials (SEPs) in the antennal nerve were recorded via an electrode inserted at the base of the antenna. It was noted that an action potential in the GF elicited an antennal twitch, which in turn evoked a mechanosensory response from the JONs in the absence of sound. We then used these extracellular recording techniques in males and female of different ages to quantify the response of the JONs to a brief sound impulse, and also to measure the strength of the connection between the JONs and the GF. At no age was there any significant difference between males and females, for any of the parameters measured. The sensitivity of the JONs to a sound impulse approximately doubled between 1 d and 10 d after eclosion, which corresponds to the period when most mating is taking place. Subsequently JON sensitivity decreased with age, being approximately half as sensitive at 20 d and one-third as sensitive at 50 d, as compared to 10 d. However, the strength of the connection between the auditory input and the GF itself remained unchanged with age, although it did show some variability that could mask any small changes.